Preliminary tests of dosimetric quality and projected therapeutic outcomes of multi-phase 4D radiotherapy with proton and carbon ion beams. (23rd November 2021) - Lis, Michelle; Newhauser, Wayne; Donetti, Marco; Wolf, Moritz; Steinsberger, Timo; Paz, Athena; Graeff, Christian
Abstract: Objective . The purpose of this study was to perform preliminary pre-clinical tests to compare the dosimetric quality of two approaches to treating moving tumors with ion beams: synchronously delivering the beam with the motion of a moving planning target volume (PTV) using the recently developed multi-phase 4D dose delivery (MP4D) approach, and asynchronously delivering the ion beam to a motion-encompassing internal tumor volume (ITV) combined with rescanning. Approach . We created 4D optimized treatment plans with proton and carbon ion beams for two patients who had previously received treatment for non-small cell lung cancer. For each patient, we created several treatment plans, using approaches with and without motion mitigation: MP4D, ITV with rescanning, static deliveries to a stationary PTV, and deliveries to a moving tumor without motion compensation. Two sets of plans were optimized with margins or robust uncertainty scenarios. Each treatment plan was delivered using a recently-developed motion-synchronized dose delivery system (M-DDS); dose distributions in water were compared to measurements using gamma index analysis to confirm the accuracy of the calculations. Reconstructed dose distributions on the patient CT were analyzed to assess the dosimetric quality of the deliveries (conformity, uniformity, tumor coverage, and extent of hotspots). Main results . Gamma index analysis pass rates confirmed the accuracy of dose calculations. Dose coverage was >95% for all static and MP4D treatments. The best conformity and the lowest lung doses were achieved with MP4D deliveries. Robust optimization led to higher lung doses compared to conventional optimization for ITV deliveries, but not for MP4D deliveries. Significance . We compared dosimetric quality for two approaches to treating moving tumors with ion beams. Our findings suggest that the MP4D approach, using an M-DDS, provides conformal motion mitigation, with full target coverage and lower OAR doses.